Technological Innovations for Superior Micro, Small, and Medium Enterprises: Transformation of Youth Organizations in the Digital Era - Fariz; Tutik Winarsih (TAAWUN, 2025)
This entrepreneurship incubation program was designed to empower the youth of Karang Taruna in Poncol Village, Magetan Regency, with the primary objective of enhancing entrepreneurial capacity and the competitiveness of local MSMEs through the integration of artificial intelligence (AI) and digital marketing. The activities were carried out using a Participatory Action Research (PAR) approach, which included the identification of needs based on local potential, Focus Group Discussions (FGDs) for co-creating digital marketing strategies, technical training on the use of AI tools (market analytics and automated content design), and competency evaluation through pre-tests and post-tests. The results demonstrated significant achievements: (1) a 42% increase in understanding of creative and innovative entrepreneurship, as measured by pre- and post-test scores; (2) improvement in the quality and quantity of MSME products through optimized digital branding and expanded marketing networks; and (3) enhanced technical proficiency in utilizing AI for data-driven marketing strategy planning. These findings indicate that technology-based youth empowerment can catalyze transforming village-based MSMEs, leading to increased competitiveness of local products in the digital market. The sustainability of this initiative requires continuous mentoring and the development of flagship products rooted in local wisdom